2014
DOI: 10.1136/bcr-2013-201567
|View full text |Cite
|
Sign up to set email alerts
|

Spotty skin pigmentation and multiple blue naevi as cutaneous markers for spinal melanotic schwannoma

Abstract: SUMMARYSpinal melanotic schwannomas are rare spinal tumours with a very poor prognosis in terms of mortality due to difficulty in complete resection and local recurrences. A 67-year-old man presented with acute onset progressive paraparesis for 2 weeks. The patient also had spotty skin pigmentations (blue naevi) in his right lateral thigh. MRI revealed an intradural extramedullary enhancing lesion in the lower thoracic cord level. With a preoperative diagnosis of simple nerve sheath tumour excision was planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…[ 20 ] MS may arise anywhere along the peripheral nerves including along the sympathetic chain, GI tract, mediastinum, and subcutaneous areas. [ 20 , 40 ] Reports on the most common locations of MS are mixed, but along the spinal nerve sheath and within the cranium are considered to be the two most common. [ 3 , 32 , 61 ] Our review of the MS literature revealed 78 cases of sporadic spinal and 20 cases of intracranial MS.[ 39 ] Fewer than 20 cases of cutaneous MS have been described.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] MS may arise anywhere along the peripheral nerves including along the sympathetic chain, GI tract, mediastinum, and subcutaneous areas. [ 20 , 40 ] Reports on the most common locations of MS are mixed, but along the spinal nerve sheath and within the cranium are considered to be the two most common. [ 3 , 32 , 61 ] Our review of the MS literature revealed 78 cases of sporadic spinal and 20 cases of intracranial MS.[ 39 ] Fewer than 20 cases of cutaneous MS have been described.…”
Section: Introductionmentioning
confidence: 99%
“…While nonpsammomatous MS is considered to be a sporadic type, encountered in fourth decades, psammomatous melanotic Schwannoma tends to occur at an earlier age (average age, 22.5 years). Psammomatous type is associated with Carney Syndrome that is characterized by the presence of myxomas in the heart, breast, uterus, skin lentigines, endocrinopathy (Cushing's syndrome), growth hormone producing pituitary adenoma, epithelioid blue nevi, Sertoli cell tumors of the testis, tumors of the thyroid, and ductal adenomas of the breast [ 1 , 4 , 6 ]. MS does not necessarily demonstrate psammoma bodies.…”
Section: Discussionmentioning
confidence: 99%
“…MS derived from the spinal nerve root is characterized by slow growth and low aggressiveness and assumes a dumbbell appearance [ 6 ]. Conventional Schwannomas are hypointense on T1-weighted and hyperintense on T2-weighted sequences, contrary to melanotic Schwannomas which are hyperintense on T1-weighted and hypointense on T2-weighted sequences [ 3 , 4 ]. Our second case was hypointense on T1-weighted and hyperintense on T2-weighted sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations